Solvent extraction in analytical geochemistry : a thesis presented in partial fulfilment of the requirements for the degree of Doctor of Philosophy at Massey University of Manawatu - Boswell, Colin Ralph (Massey University, 1966)
A procedure conbining solvent extraction enrichment techniques and spectrographic analysis was developed for the quantitative determination of many trace elements in a wide range of silicate rocks and in a series of highly saline Antarctic lake waters. Since a great deal of the work depended on spectrographic analysis, an investigation was carried out to improve the precision and sensitivity of existing methods. An improved method for the determination of spectralline intensities was developed. This was based on the author's nodification of the partial Seidel function, referred to as B-functions. A conversion table for these is given. A scale calibrated in B-functions was incorporated into a Hilger microphotometer enabling such values to be obtained directly without the use of conversion tables. B-values can be plotted directly onto the linear ordinate of semilog paper if the self-calibration method is used for evaluating line intensities. This results in a straightening of the characteristic curve with an attendant time saving and an improvement in the accuracy of the background extrapolation. A nomographic technique was also developed for use in conjunction with this scale and resulted in a rapid evaluation of line intensities but with some loss in precision. Cathode excitation as distinct from cathode layer was compared with anode excitation under the same conditions. Data on 33 elements were used to study relative self-absorption effects, absolute sensitivities, volatilisation curves, times for complete combustion and background effects. Data on14 elements and 35 line pairs were used to study reproducibilities in the three matrices, NaCl, CaCl2 and carbon. It was shown that cathode excitation in a carbon matrix afforded the greatest precision for a number of the more volatile elements. Anode excitation provided generally better precision if a NaCl matrix was used. CaCl2 was a very unsatisfactory rnatrix. For the more volatile elements cathode excitation provided a higher sensitivity than anode excitation but with increased background and cyanogen emission. The extraction of the elements Au,Zn,Cd,Hg, Ga, In,Tl,Sn,Pb,As,Sb and Bi from hydrochloric acid into the three solvents cyclohexanone, cyclohexanol and cyclohexane was studied as a function of acid concentration. Cyclohexanone is a more efficient, but less selective extractant, than cyclohexanol. Cyclohexane has little extracting power for these elements. Solvent extraction of hydrochloric acid solutions of a series of highly saline Antarctic lake waters into cyclohexanone was used to enrich the elements Zn,Pb, In, Bi, Fe, Mn, Mo prior to spectrographic analysis. For this, the percent extraction of Fe, Mn and Mo into cyclohexanone from 3N hydrochloric acid was obtained. This investigation has shown that one of these lakes, Lake Bonney, has most probably had a seawater origin. It is also possible that another of these lakes, Lake Fryxell, may also have contained seawater in the past. From the relative abundance of the various elements in the other lakes, it was possible to conduct a geochemical reconnaissance of the areas surrounding the lakes. This suggested that the two most likely areas for mineralisation in the McMurdo Oasis area of Antarctica are the region surrounding and feeding water to Lake Hoare and the region surrounding Lake Joyce. A consideration of the theory of discontinuous counter current liquid-liquid extraction has shown that it is possible to simultaneously determine the extraction characteristics of a large number of elements for a given solvent system. If this technique is coupled with spectrographic analysis the determination is particularly rapid. The extraction of the elements Ti, V, Cr, Mn, Fe, Co, Ni, Zn, Ga, As, Nb, Mo, Ru, Rh, Pd, Ag, Cd, In, Sn, Sb, La, W, Re, Os, Ir, Pt, Au, Hg, Tl, Pb and Bi from hydrochloric acid into methyl isobutyl ketone was studied as a function of acid concentration. The data were obtained by studying spectrographically the distribution patterns of the elements after equilibration on a discontinuous counter current liquid-liquid extraction apparatus. A comparison of some of the data so obtained with results for the same system as reported by other workers showed that the technique is valid and accurate. Using these data it was possible to devise a scheme which could separate Fe from the majority of the trace elements extracted by cyclohexanone from a hydrochloric acid solution of a rock. By a combination of batch extraction with cyclohexanone and counter current distribution with methyl isobutyl ketone it was possible to obtain quantitative data for Zn and Ga and semiquantitative data for In in a wide range of silicate rocks by spectrochemical analysis. By the use of extraction into cyclohexanone coupled with atomic absorption spectrometry it was possible to determine the concentration of Pb, Cd and Bi in the same suite of rocks. By the use of these techniques it wa spossible to obtain fresh abundance data for the above elements in the four standard rocks,G-1, W-1 CAAS syenite and CAAS sulphide. The cyclohexanone/hydrochloric acid extraction system provides a satisfactory enrichment technique for the spectrographic analysis of trace elements in material with a low Fe content. For material containing a high concentration of Fe, it is necessary to combine this technique with discontinuous counter current liquid-liquid extraction to separate the Fe before spectrographic analysis. However, under these conditions, certain elements can be determined by direct atomic absorption spectrometry of the cyclohexanone extract.
Content removed due to copyright restrictions: Boswell, C. R., & Brooks, R. R. (1965). Improved Methods for the Measurement of Spectral Line Intensities. Applied Spectroscopy, 19(5), 147. Brooks, R. R., & Boswell, C. R. (1965). A comparison of cathode and anode excitation in the d.c. arc. Analytica Chimica Acta, 32(C), 339-345. Boswell, C. R., & Brooks, R. R. (1965). The extraction of elements with cyclic solvents and its application to geochemical analysis. Analytica Chimica Acta, 33(C), 117-122. Boswell, C. R., & Brooks, R. R. (1965). The application of discontinuous, countercurrent, liquid-liquid extraction to the study of the distribution of metal ions between hydrochloric acid and methyl isobutyl ketone. Mikrochimica Acta, 53(5-6), 814-821.
Keywords: Solvent extraction; Silicate rocks; Geochemistry